Agomelatine: mechanism of action and pharmacological profile in relation to antidepressant properties - Guardiola-Lemaitre, B (Blackwell Publishing Ltd, 2014)
Agomelatine behaves both as a potent agonist at melatonin MT(1) and MT(2) receptors and as a neutral antagonist at 5-HT(2C) receptors. Accumulating evidence in a broad range of experimental procedures supports the notion that the psychotropic effects of agomelatine are due to the synergy between its melatonergic and 5-hydroxytryptaminergic effects. The recent demonstration of the existence of heteromeric complexes of MT(1) and MT(2) with 5-HT(2C) receptors at the cellular level may explain how these two properties of agomelatine translate into a synergistic action that, for example, leads to increases in hippocampal proliferation, maturation and survival through modulation of multiple cellular pathways (increase in trophic factors, synaptic remodelling, glutamate signalling) and key targets (early genes, kinases). The present review focuses on the pharmacological properties of this novel antidepressant. Its mechanism of action, strikingly different from that of conventional classes of antidepressants, opens perspectives towards a better understanding of the physiopathological bases underlying depression.